Isolation, characterization, and expression of the Corynebacterium glutamicum betP gene, encoding the transport system for the compatible solute glycine betaine. - Peter, H (1996)
Corynebacterium glutamicum accumulates glycine betaine under conditions of high osmolarity. Previous work revealed the existence of a high-affinity glycine betaine permease which is osmotically regulated. In the present study, the corresponding gene was cloned. The betP gene, encoding the glycine betaine uptake carrier, was isolated by heterologous complementation of mutant strain Escherichia coli MKH13. From sequence analysis it is predicted to encode a protein of 595 amino acids. This protein shares 36% identity with the choline transport system BetT and 28% identity with the carnitine transport system CaiT of E. coli, as well as 38% identity with a protein with an unknown function from Haemophilus influenzae. Analysis of hydropathy indicated a common structure for all four transport proteins. After heterologous expression of betP in E. coli MKH13, the measured Km values for glycine betaine and the cotransported Na+ were similar to those found in C. glutamicum, whereas the modulation of activity by osmotic gradients was shifted to lower osmotic values.